Efektivitas Pemberian Asam Amino dan Kombinasi Media Tanam Terhadap Pertumbuhan Tanaman Lidah Buaya (Aloe barbadensis Milleer) - Handayani, Turi; Lubis, Ade Fipriani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Effectiveness of Providing Amino Acids and Planting Media Combinations on the Growth of Aloe Vera Plants (Aloe barbadansis Milleer). This research will be carried out at AFD VI Pamerahan, Perkebunan. Air Batu III/IX Hamlet V, Air Batu District, Asahan Regency and will be held from December to February 2024 at a height of 12 m above sea level. This research was structured based on a factorial randomized block design (RAK) with 2 treatment factors and 3 replications. The first factor is that amino acids consist of 4 levels, including A0 = 0 ml/polybag, A1 = 2 ml/polybag, A2 = 4 ml/polybag, A3 = 6 ml/polybag. The second factor is that the planting medium consists of 4 levels, including M0 = topsoil + sand, M1 = topsoil + compost,    M2 = topsoil + vermicompost, M3 = topsoil + bokashi.Providing amino acids had a significant effect on the parameters of plant height, number of leaves, longest leaf length, widest leaf width, total wet weight. Amino acid dosage treatment showed a significant effect on plant height parameters, where the best treatment resulted in treatment A3, namely 6 ml/polybag which had a plant height of 14.41 cm, number of leaves of 8.25, longest leaf length of 18.74 cm, width The widest leaves are 6.25 cm, total wet weight is 133.29 g. The combination of planting media influences the parameters of plant height, number of leaves, longest leaf length, widest leaf width, total wet weight. The combination treatment of topsoil + compost (M1) planting media had a plant height of 13.95 cm, number of leaves of 8.91, leaf length of 20.54 cm, leaf width of 6.00 cm, total wet weight of 131.54 g. The interaction of amino acid administration and the combination of planting media had no effect on all observed parameters Keywords:  amino acid, aloe vera, planting media  Abstrak: Efektivitas Pemberian Asam Amino dan Kombinasi Media Tanam Terhadap Pertumbuhan Tanaman Lidah Buaya (Aloe barbadansis Milleer). Penelitian ini akan dilaksanakan di AFD VI Pamerahan, Perkebunan. Air Batu III/IX Dusun V Kecamatan Air Batu Kabupaten Asahan dan dilaksanakan pada bulan Desember sampai Februari 2024 dengan ketinggian 12 m dpl. Penelitian ini disusun berdasarkan Rancangan Acak Kelompok (RAK) Faktorial dengan 2 faktor perlakuan dan 3 ulangan. Faktor pertama adalah asam amino terdiri dari 4 taraf, diantaranya A0 = 0 ml/ polibag, A1 = 2 ml/ polibag, A2  = 4 ml/ polibag, A3 = 6 ml/ polibag. Faktor kedua adalah media tanam terdiri dari 4 taraf, diantaranya M0 = topsoil + pasir, M1 = topsoil + kompos, M2 = topsoil + kascing, M3 = topsoil + bokashi.Pemberian asam amino berpengaruh nyata terhadap parameter tinggi tanaman, jumlah daun, panjang daun terpanjang, lebar daun terlebar, berat basah total. Perlakuan dosis asam amino menunjukkan berpengaruh nyata pada parameter tinggi tanaman, dimana perlakuan yang terbaik dihasilkan perlakuan A3 yaitu 6 ml/ polibag yang memiliki tinggi tanaman 14,41 cm, jumlah daun sebanyak 8,25 helai, panjang daun terpanjang 18,74 cm, lebar daun terlebar 6,25 cm, berat basah total sebanyak 133,29 g. Kombinasi media tanam berpengaruh terhadap parameter tinggi tanaman, jumlah daun, panjang daun terpanjang, lebar daun terlebar, berat basah total. Perlakuan kombinasi media tanam tanah topsoil + kompos (M1) memiliki tinggi tanaman 13,95 cm, jumlah daun sebanyak 8,91 helai, panjang daun sepanjang 20,54 cm, lebar daun 6,00 cm, berat basah total 131,54 g. Interaksi pemberian asam amino dan kombinasi media tanam tidak berpengaruh terhadap semua parameter pengamatan. Kata kunci: asam amino, aloe vera, media tanam